Uji Stabilitas Metformin dan Penghilangannya dari Air oleh Zeolit ​​Berbasis Batu Apung - Vicky Prajaputra; Nadia Isnaini (Postgraduate, University of Mataram, 2023)
Metformin (MET) is an emerging contaminant often found in aquatic environments due to incompletely metabolized after consumption in the human body, where some of its doses are excreted in unchanged form through urine or faeces. The research aims are to study MET stability in water and to evaluate the potential of pumice-based zeolite for treating MET contaminants. Zeolites were prepared from pumice via the hydrothermal treatment and characterized using Fourier Transform Infrared (FTIR) and X-Ray Diffraction (XRD). A simple spectrophotometric method was proposed for determining the stability of MET in aqueous solution with several different conditions. The result showed that the metformin solution was unstable under strong acid conditions (pH 2), marked by the loss of the maximum absorption peak in the 220-250 nm range. The stable metformin conditions in this study were obtained at the pH of solutions ranging from 6 to 10 and temperatures between 14 oC to 40 oC. Furthermore, the stability of MET can be maintained for up to 3 days of exposure time. Based on the adsorption result, zeolite uptake capacity (196 µg/g) was higher than pumice (87 µg/g) to reduce metformin concentration. In addition, the synthesized zeolite needs further modification to increase its adsorption performance.